Analisis Kualitas Butir Soal Mata Pelajaran Ekonomi Berdasarkan Item Response Theory (Kasus pada SMAN 11, SMAN 18, dan SMAN 23 Bandung) - Suchia Aulia Saputri (Jurnal Pendidikan Ekonomi Indonesia, 2022)
This study discusses the quality of items based on Item Response Theory at the end of the semester assessment odd Class XI IPS in SMA Negeri 11, SMAN 18 and SMAN 23 Bandung. The purpose of this study was to determine the quality of the items of economic subjects odd fitting. PAS is one of the tests used to measure the success of the teaching and learning process in one semester. The test items tested are question items created by the teacher and must be of good quality so it is necessary to analyze the quality of the items using the Item response theory. The research method used is descriptive analysis through quantitative approach. The study involved 427 student responses, and 85 questions from 3 schools. Item quality analysis is based on Item response theory which measures 2 logistic parameters (difficulty level and differentiation) with the help of Quest Software. The result of this study are the quality of items on economics subjects Class XI IPS SMA Negeri 11, SMAN 18, and SMAN 23 Bandung based on Item Response Theory as a whole there are only 33 items of good quality, 47 items of poor quality, and 5 items of poor quality. Based on the validity and reliability, there are 80 valid items and 5 invalid items, and has an item reliability value of more than 0.85 which means that the test items can be used to determine the individual student's decision.